THE PROBLEM OF THE EMOTIONAL INTELLIGENCE FORMATION OF MODERN YOUTH THROUGH THE PRISM OF VASYL STEFANYK’S CREATIVITY - Savchuk, Borys; Pantyuk, Tetyana; Dovgij, Oleg; Vysochan, Lesia (Mountain School of Ukrainian Carpaty, 2021)
Scientists have made an in-depth analysis of the scientific and theoretical foundations of emotional intelligence. The purpose of the article is to analyze the problem of the emotional intelligence formation of modern youth through the prism of Vasyl Stefanyk’s creative heritage. The main concept of our study is to analyze the work and figure of Vasyl Stefanyk through the prism of the phenomenon of emotional intelligence. Our analysis is based on the classic Bar-On model. Reuven Bar-On made a significant contribution to its development. He developed the EQ-i (Emotional Quotient Inventory) test in 1996. It contains a list of questions to determine its ratio. a «Bar-On model» serves on this basis as one of the methodological components of our research. It determines the level of formation of EQ on the basis of a person’s possession of 15 abilities:1) self-esteem – awareness and self-assessment of their capabilities and limitations, strengths and weaknesses, self-perception «as I am»; 2) emotional awareness – understanding of emotional state and the reasons for its occurrence; 3) self-expression – a clear, constructive expression of their feelings, thoughts, ability to mobilize emotional energy, show the firmness of beliefs; 4) independence – reliance on their own strength, emotional independence; 5) empathy – recognition, understanding and awareness of the feelings of another person; 6) social responsibility – selfidentification as a member of a social group, constructive cooperation, care and responsibility for themselves and others; 7) interpersonal relationships – the establishment of mutually beneficial relationships based on emotional intimacy, comfortable behavior in social contacts; 8) resistance to stress – effective management of their emotions, a quick way out of difficult situations; 9) control of impulses – restraint of emotions; 10) assessment of reality – the comparison of feelings and thoughts with objective reality; 11) flexibility – adjustment of feelings, thoughts, ideas, behavior in accordance with circumstances; 12) problem solving – finding out the essence and finding ways to solve it effectively; 13) self-actualization – setting goals and striving to achieve it on the basis of potential; 14) optimism – emotional balance, positive attitude and maintaining hope in any situation; 15) happiness / well-being – a sense of satisfaction with others, life in general. Thus, we believe that such a reflection on the work of V. Stefanyk should encourage some changes in the emphasis on the formation of the idea of the writer himself.